Persuasion In Advertisements Of Freight Forwarding - Galuh Dynasty Mula Suparma; Chatarini Septi Ngudi Lestari (International Journal of Linguistics and Discourse Analytics, 2021)
This study is concerned with persuasion in advertisements of freight forwarding which were uploaded within 2019 on YouTube based on discourse analysis perspective. This study aims to find out the kinds of persuasive strategies and the way how persuasions are used. To reach those goals, Beebe & Beebe’s theory of persuasive strategies and Makosky’s theory of persuasion technique are applied. Qualitative research employed since the data are in the form of words, phrases, or even sentences. The result showed that the kind of persuasive strategy which mostly performed in freight forwarding advertisements is causal reasoning (49). Moreover, the way of using persuasion in the form of persuasion technique which mostly applied is the appeal to or creation of needs (92)